A primer on critical thinking and business ethics : critical thinking applied to business management (volume 2) - Mascarenhas, Oswald A. J.; Thakur, Munish; Kumar, Payal (Emerald Publishing Limited, 2024)
A Primer on Critical Thinking and Business Ethics: Critical Thinking Applied to Business Management (Volume 2) encapsulates new developments in Critical Thinking skills for MBA students, in the form of a broad-based cross disciplinary primer in business management, with a special focus on business ethics. Each volume encourages critical thinking as a higher order type of thinking that can be taught, leading to a life of rationality, ethics and empathy, which is urgently required of leaders in a global environment where fraud and corruption are rife. Volume 2 explores: Critical Thinking as applied to free market enterprise capitalism; to profit maximization presumptive models of capitalist thinking; to challenges of student assurance of learning; for owning moral responsibility for turbulent markets; and to domesticate global social 'wicked' problems. It is essential reading for all MBA students, as well as for researchers and practitioners.
Includes index.
Keywords: Critical thinking.; Industrial management.; Business ethics.; Business & Economics -- Industrial Management.; Management decision making.; Management and management techniques.; elektronické knihy; electronic books